Autoimmune hemolytic anemia: classification and therapeutic approaches. Issue 2 (December 2008) - Sève, Pascal; Philippe, Pierre; Dufour, Jean-François; Broussolle, Christiane; Michel, Marc
Autoimmune hemolytic anemia (AIHA) is a relatively uncommon cause of anemia. Classifications of AIHA include warm AIHA, cold AIHA (including mainly chronic cold agglutinin disease and paroxysmal cold hemoglobinuria), mixed-type AIHA and drug-induced AIHA. AIHA may also be further subdivided on the basis of etiology. Management of AIHA is based mainly on empirical data and on small, retrospective, uncontrolled studies. The therapeutic options for treating AIHA are increasing with monoclonal antibodies and, potentially, complement inhibitory drugs. Based on data available in the literature and our experience, we propose algorithms for the treatment of warm AIHA and cold agglutinin disease in adults. Therapeutic trials are needed in order to better stratify treatment, taking into account the promising efficacy of rituximab.